High Performance Liquid Chromatographic Studies of Teriflunomide: Method Development and Validation for Drug Development and Formulation - Uttam Prasad Panigrahy, (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: There is an unmet analytical need to develop a rapid, robust, and precise method for teriflunomide in drug development and research in pharmaceutical formulations. The main spotlight of this research work is to develop a precise, simple, and accurate method for the application of analytical research development of teriflunomide and its pharmaceutical formulations. Materials and Methods: The quantification and analytical validation of teriflunomide was developed with a stationary phase XBridge column C18 (4.6 mm × 250 mm, 5 µm) and LC1120 Agilent high performance liquid chromatographic instrument equipped with variable wavelength detector at 294 nm and Acetonitrile: Buffer containing 20 mM of Ammonium acetate and 5 mL glacial acetic acid with pH adjustment 4.48 (60:40, v/v) was used as mobile phase passed at a flow rate 1 mL/min. Elution takes place at a retention time of 2.853 min. Results and Discussion: Validation of the method was performed as per International Council for Harmonisation guidelines, which shows linearity concentration range from 10 to 60 µg/mL amid correlation coefficient = 0.999 with Y = 78737 × +47703 regression equation was obtained. Accuracy of the proposed method was established to 99.03–99.13% with relative standard deviation (% RSD) values <2%. Method precision, system precision, and reproducibility % RSD value were 0.14%, 0.23%, and 0.14%, respectively. The limit of detection and limit of quantitation of teriflunomide were 0.06 µg/mL and 0.2 µg/mL, correspondingly. The intermediate precision was carried out and the results of Teriflunomide were achieved <2% RSD. Robustness was performed by deliberate changes in wavelength and flow rate and the results of robustness were achieved <2% RSD. Conclusion: The developed method was precise, simple, and accurate for the application of analytical research development of teriflunomide and its pharmaceutical formulations.